A Priori Model of Constitutionality Review in Georgia: Systemic Aspects and Potential Shortcomings - Zaza Tavadze (European Scientific Journal, ESJ, 2018)
The genesis of a priori review of legislation traces back to France, which was devised with a clear objective to ensure institutional balance and separation of powers between government branches. This model has spread all across Europe, including Georgia. The present paper, by applying analytical research methodology, aims to dwell on some of the institutional characteristics of constitutional system in Georgia and underscore potential difficulties of a priori review model that could be associated with its functioning in practice.